Analisis Pengaruh Kualitas Layanan, Perluasan Merek Terhadap Citra Merek dan Loyalitas Pelanggan Sepeda Motor (Study Kasus Pada Kawasaki PT Makmur Auto Mandiri Manado) - Sahetapy, jeofer Pratama (JURNAL RISET BISNIS DAN MANAJEMEN, 2015)
The purpose of this research is to know the quality of services impact on brand image , the expansion of the brand impact on brand image , the quality of services of its effect on customer loyalty , the expansion of the brand impact on customer loyalty , and image brand impact on customer loyalty. The research results show that: The quality of services it has some positive effects and significantly to brand image , The expansion of the brand it has some positive effects and significantly to brand image, The quality of services it has some positive effects and significantly to customer loyalty,The expansion of the brand have had a positive impact but not significantly to customer loyalty, andÂ  Brand image influential positive and significant against customer loyalty. Keywords: service quality, brand extension, brand image, customer loyalty